Microstructural differences of oxide layer on Si-containing austenitic stainless steel exposed to oxygen-saturated and oxygen-poor LBE - Hao Ren; Xiaoxin Zhang; Xian Zeng; Xiaodong Huang; Decang Zhang; Jun Zhang; Qingzhi Yan (Journal of Materials Research and Technology)
Increasing the content of Si element in austenitic stainless steels is a strategic approach to improve their dissolution corrosion resistance in liquid lead-bismuth eutectic (LBE) at elevated temperature. In this work, a Si-modified austenitic steel was exposed to static liquid LBE with saturated and 10−8 wt.% oxygen concentration at 600 °C for up to 3000 h. After exposing to oxygen-saturated LBE, the oxide scale formed on Fe–Cr–Ni–Si steel comprises a multi-layer structure, including Fe–Cr spinel, magnetite and PbFe4O7. A large number of SiO2 nanoparticles with a size of ∼200 nm are observed in FeCr2O4 oxide film. In contrast, for the samples immersing in liquid LBE with 10−8 wt.% oxygen concentration, amorphous SiO2 bands rather than nanoparticles are distributed among Cr2O3 oxides in IOZ. The dense Si-rich oxide film hinders the dissolution corrosion of HLM on austenitic steel. Meanwhile, the low oxygen concentration in LBE suppresses the formation of magnetite and promotes the growth of SiO2 into a more continuous banded oxides than nanoparticles.